Analysis of Character and Characterization of Main Character in Novel After (2019) By Anna Todd - Ramadhani, Eka Syafira; Rohmana, Wahyu Indah Mala (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This research aims to explore the characterization of the two main characters in Anna Todd's novel After (2019): Tessa Young and Hardin Scott. By utilising data collected from the text of the novel, along with supplementary internet research, the study delves into various intrinsic elements such as character development, themes, and setting. This comprehensive analysis reveals that characterization encompasses a range of aspects, including a character's attitude, physical traits, actions, speech patterns, and perspectives on the challenges they encounter throughout the narrative.Through a detailed examination of Tessa and Hardin, the research highlights how their individual complexities and growth contribute significantly to the overarching themes of love, trust, and emotional conflict in the story. The findings underscore the importance of understanding character dynamics in literature, as these dynamics play a crucial role in shaping readers' engagement and interpretation of the narrative. Ultimately, this study provides valuable insights into how character development influences the reader's experience, showcasing the depth of Todd's work and its exploration of the intricacies of human relationships.